Equação do 1 grau. Qual a reposta de 5(1-×)-2×+1=-3 (2+×)
Soluções para a tarefa
Respondido por
4
5-5x-2x+1=-6-3x
-7x+3x=-6-6
-4x=-12
4x=12
x=12/4
x=3
-7x+3x=-6-6
-4x=-12
4x=12
x=12/4
x=3
Jeninha0407:
Obrigado.
Respondido por
6
Olá,
5(1-×)-2×+1=-3 (2+×)
5 - 5x - 2x + 1 = - 6 - 3x
- 5x - 2x + 3x = - 6 - 5 - 1
- 7x + 3x = - 12
- 4x = - 12 multiplique os dois termos por - 1
4x = 12
x = 12/4
x = 3
===============
bons estudos.
5(1-×)-2×+1=-3 (2+×)
5 - 5x - 2x + 1 = - 6 - 3x
- 5x - 2x + 3x = - 6 - 5 - 1
- 7x + 3x = - 12
- 4x = - 12 multiplique os dois termos por - 1
4x = 12
x = 12/4
x = 3
===============
bons estudos.
Conheça o regulamento =
https://brainly.com.br/pages/regulamentoPerguntas interessantes
Biologia,
11 meses atrás
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Administração,
1 ano atrás
Matemática,
1 ano atrás